Determinan Kualitas Laporan Keuangan Pemerintah Daerah dengan Sistem Pengendalian Internal sebagai Variabel Moderasi - Yaya, Rizal; Ramadhani, Nadia (Akuntansi & Ekonomika, 2024)
The aim of this research is to see how the quality of local government financial reports, with the internal control system as a moderating variable, is influenced by the use of technology, good governance, and human resource competence. This research is motivated by the increasing cases of corruption, bribery, low integrity and fraud in the administration of regional government. This quantitative research uses primary data and purposive sampling method involving 98 employees of the finance subsection of Regional Apparatus Organizations. The smartPLS v3.0 application allows analysis to test this research hypothesis. The research results show that good governance and human resource competence improve the quality of financial reports. Likewise, the internal control system strengthens the influence of information technology on the quality of financial reports. However, the use of information technology does not affect the quality of financial reports.